(untitled) (Research, Society and Development, 2022)
Several foods are available for the formulation of rations in Brazil; however, the effectiveness of a few of these foods has been evaluated in diets for bullfrog tadpoles (Lithobates catesbeianus). This study aimed to evaluate alternative foods (worm meal, peeled banana, peeled pumpkin, and peeled avocado) with different levels of crude protein and ether extract for the nutrition of bullfrog tadpoles to obtain the best animal performance and water quality. In a 60 days long experiment, a total of 480 bullfrog tadpoles (stage 25 of the Gosner table, 1960) with an average weight of 0.107 ± 0.004 g, were used. The experimental design was completely randomized (DIC) in a factorial scheme (2x2) with four treatments [rations with 320 g/kg crude protein (CP) and 90 g/kg ether extract (EE); 380 g/kg CP and 90 g/kg EE; T3:320 g/kg CP and 110 g/kg EE; 380 g/kg CP and 110 g/kg EE] each consisting of four replicates. To verify the normality of the data, the results of zootechnical performance, water quality, and proximate composition were subjected to the Shapiro-Wilk and Bartlett tests. Analysis of variance (ANOVA) was then performed, and the means were compared using Duncan’s test at 5% of probability. The verified results of animal performance, water quality, and proximate composition were not influenced by the suggested diets. The best diet formulated based on easily acquired alternative ingredients can offer 320 g/kg CP and 90 g/kg EE to the tadpoles of bullfrog.